Analisis Kepuasan Santri Putri An-Nawawi Berjan Purworejo Terhadap Kualitas Produk Pajegan: Perspektif Hukum Ekonomi Syari’ah - Imam Turmudi (CV. Ulil Albab Corp, 2024)
This study aims to analyze the contract used in the sale and purchase of Pajegan and to find out the influence of the quality of Pajegan products on the satisfaction of female students at Pondok Pesantren An-Nawawi Berjan Purworejo. In this study, researchers used quantitative and qualitative research methods. The results of the research on the contract used in the sale and purchase of pajegan at the An-Nawawi Islamic Boarding School is the bai' al-mu'athah contract. This study uses a simple random sampling technique with a sample of 79 respondents. It can also be seen that the results of tcount (160.035) > ttable (0.1864) which means that Ha is accepted and there is a significant influence between student satisfaction on the quality of Pajegan products. Based on the results of research that has been carried out, it can be concluded that there is a significant influence between student satisfaction on the quality of Pajegan products. From these results, the coefficient of determination is 17.16% and the remaining 82.84% is influenced by other factors not explained in this research variable, such as environmental factors, daily life of students, and others.